2020
DOI: 10.1155/2020/2412396
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Efficacy and Safety of Induction Therapies for the Treatment of Patients with Proliferative Lupus Nephritis in South Africa

Abstract: Background. Lupus nephritis (LN) can be complicated with requirement for kidney replacement therapy and death. Efficacy of induction therapies using mycophenolate mofetil (MMF) or intravenous cyclophosphamide (IVCYC) has been reported from studies, but there is limited data in Africans comparing both treatments in patients with proliferative LN. Methods. This was a retrospective study of patients with biopsy-proven proliferative LN diagnosed and treated with either MMF or IVCYC in a single centre in Cape Town,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…Similarly, the current results found no significant difference in the recorded rate between both treatment groups, which is consistent with what has been reported by Sogayise et al 21 Our findings are congruent with those of Sahay et al 22 , who examined the efficacy of three LN therapy regimens (ELNT, NIH, and MMF). The European Lupus Nephritis Trial (ELNT) regimen included six 500 mg IV CYC doses given biweekly, but the National Institute of Health (NIH) regimen included 0.5 g/m 2 monthly treatment for six months, with MMF given at a dosage of 1200 mg/m 2 .…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, the current results found no significant difference in the recorded rate between both treatment groups, which is consistent with what has been reported by Sogayise et al 21 Our findings are congruent with those of Sahay et al 22 , who examined the efficacy of three LN therapy regimens (ELNT, NIH, and MMF). The European Lupus Nephritis Trial (ELNT) regimen included six 500 mg IV CYC doses given biweekly, but the National Institute of Health (NIH) regimen included 0.5 g/m 2 monthly treatment for six months, with MMF given at a dosage of 1200 mg/m 2 .…”
Section: Discussionsupporting
confidence: 93%
“… 23 Many cases of SLE are complicated by various infections attributable to the primary disease or compromised immune function caused by drug treatment. 24 , 25 Differentiating infections from high disease activity is crucial in patients with autoimmune diseases such as SLE. 26 , 27 …”
Section: Discussionmentioning
confidence: 99%
“…23 Many cases of SLE are complicated by various infections attributable to the primary disease or compromised immune function caused by drug treatment. 24,25 Differentiating infections from high disease activity is crucial in patients with autoimmune diseases such as SLE. 26,27 Our study demonstrated that pulmonary infection was most common, followed by urinary and intestinal infection, which was consistent with the results of other research.…”
Section: Discussionmentioning
confidence: 99%